Information visualization perception for design - Ware, Colin (San Francisco, CA : Morgan Kaufman, 2004)
Most designers know that yellow text presented against a blue background reads clearly and easily, but how many can explain why, and what really are the best ways to help others and ourselves clearly see key patterns in a bunch of data? This book explores the art and science of why we see objects the way we do. Based on the science of perception and vision, the author presents the key principles at work for a wide range of applications--resulting in visualization of improved clarity, utility, and persuasiveness. The book offers practical guidelines that can be applied by anyone: interaction designers, graphic designers of all kinds (including web designers), data miners, and financial analysts. *First work to use the science of perception to help serious designers and analysts optimize understanding and perception of their data visualizations. * Major revision of this classic work, with a new chapter on visual thinking, new sections on face perception and flow visualization, and a much expanded chapter on color and color sequences. *New to this edition is the full color treatment throughout, to better display over 400 illustrations.
Foundation for a science of data visualization -- Environment, optics, resolution, and the display -- Lightness, brightness, contrast, and constancy -- Color -- Visual attention and information that pops out -- Static and moving patterns -- Visual objects and data objects -- Space perception and the display of data in space -- Images, words, and gestures -- Interacting with visualizations -- Thinking with visualization.
Includes bibliographical references (p. 405-449) and indexes.
Keywords: Quality control; Information visualization -- Data processing; Engineering inspection; Electronic books